The Development of Melodic Recitation Skills in Thai Poetry Using the Think-Pair-Share Technique Integrated with a Creative Learning Model for Grade 5 Students at Wat Khaenai School - คำพันธ์, ทรงสิทธิ์; บัวสำอางค์, พานิช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) develop the rhythmic reading skills of Thai poetry (Thai Melodious Recitation) among Grade 5 students using the Think-Pair-Share (TPS) technique integrated with Creative Learning; 2) compare students' rhythmic reading abilities before and after the intervention; and 3) investigate student satisfaction toward this instructional approach. The study employed a quasi-experimental research design. The sample group consisted of 25 Grade 5B students, selected through cluster random sampling. The research instruments included: 1) lesson plans utilizing the Think-Pair-Share technique combined with Creative Learning; 2) a recitation performance record for the main poetic text "Knowledge is Like Merchandise" (Wicha Muean Sinkha) to track skill development during the lessons; 3) a rhythmic reading proficiency test; and 4) a student satisfaction questionnaire. Data were analyzed using mean ($\bar{x}$), standard deviation (S.D.), and dependent samples t-test.• After the instruction, students achieved an average score of 85.90% in melodious intonation reading, which exceeded the set criterion of 80% in all aspects.• The melodious intonation reading skills of Prathomsuksa 5 students, after receiving instruction using the Think-Pair-Share technique combined with the constructivist learning model, were significantly higher than before the instruction at the .05 statistical level.• The overall satisfaction of the students towards the instruction using the Think-Pair-Share technique combined with the constructivist learning model yielded an average mean score of 4.99, which corresponds to the Highest Agreement level.